Tindak Pidana Pemerkosaan Terhadap Anak Di Bawah Umur Di Kota Ambon - Wuarlela, Fransina; Toule, Elsa Rina Maya; Salamor, Anna Maria (PATTIMURA Law Study Review, 2024)
ABSTRACT: Children need to receive more serious attention from the Indonesian government. This happens because there is still a tendency that child victims are still neglected by the government and component institutions of the criminal justice system. Every person has the right to be treated fairly and have their rights protected as stated in article 28 of the 1945 Constitution of the Republic of Indonesia. The problems raised in this writing are: how is criminal responsibility for the crime of rape against minors, and how to protection from violence against children in Ambon City. The research method used is Normative Law research or library research. This means that legal research examines document studies, which are in the form of various primary laws such as statutory regulations, court decisions, legal theories and can be in the form of scholarly opinions. The results of the research can be concluded that criminal responsibility for rape cases is regulated in Article 285 of the Criminal Code with imprisonment and a maximum penalty of life imprisonment. Efforts to protect against violence against children are carried out in a penal and non-penal manner. Penalty is a repressive countermeasure carried out after a crime occurs by enforcing the law and imposing punishment. Actions taken to overcome this are through coaching and rehabilitation measures. Non-penal is a preventive response effort with actions in the form of prevention before a crime occurs. This action is carried out through socialization, familiarization with the law, and improvement of businesses.